A pilot investigation of the prevalence of US-detectable forefoot joint pathology and reported foot-related disability in participants with systemic lupus erythematosus. Issue 1 (December 2016) - Mukherjee, Sandeep; Cherry, Lindsey; Zarroug, Jalaa; Culliford, David; Bowen, Catherine; Arden, Nigel; Edwards, Christopher
Abstract Background The main aim of this study was to determine the prevalence of US-detectable forefoot bursae, metatarsophalangeal (MTP) joint and metacarpophalangeal (MCP) joint synovial hypertrophy (SH), Power Doppler (PD) signal or erosion in participants with systemic lupus erythematosus (SLE). A secondary aim was to determine the strength of potential association between patient reported foot-related disability and US-detected forefoot bursae, MTP joint SH, PD signal or erosion in participants with SLE. Method A cross-sectional observational study of 20 participants with SLE was completed to determine the prevalence of US-detected forefoot bursal, MTP and MCP joint pathology. Patient-reported foot-related impairment and activity limitation (accumulatively referred to as disability) were also recorded. Spearmans' Rank Correlation analyses were completed to determine the potential strength of association between US-detected pathology and patient report disability. Results The prevalence of MTP joint SH and PD was 80 % (16/20) and 10 % (2/20), respectively. The prevalence of MCP joint SH and PD was 60 % (12/20) and 30 % (6/20) respectively. A significant association was noted between PD scores for the MTP joints and MCP joints (r  = 0.556;p  = 0.011) although this was not demonstrated for SH scores (r  = 0.176;p  = 0.459). Significant associations between forefoot bursal prevalence and MTP joint PD were noted (r  = 0.467;p  = 0.038). The prevalence of bursae and bursal PD (grade 2 or above) was 100 % (20/20) and 10 % (2/20), respectively. Moderate foot-related impairment and activity limitation was reported by 95 and 85 % of participants respectively. Conclusion This pilot study suggests that US-detected MTP, MCP joint and forefoot bursal abnormalities may be prevalent in participants with SLE and they may experience a moderate level of foot-related disability. Further research is required to substantiate these preliminary findings.